Uji Aktivitas Antioksidan Kombucha Daun Alpukat (Persea americana Mill.) Berdasarkan Lama Fermentasi dengan Metode ABTS - Andry, Muhammad; Karo-Karo, Sry Ulina; Lubis, Indah Pertiwi; Lubis, Ervina Syahfitri; Lubis, Meiva Amalia; Nasution, Halimnah Raina (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Kombucha tea is a widely consumed herbal beverage. Avocado leaves (Persea americana Mill.) are known to contain various bioactive compounds such as flavonoids, quercetin, and polyphenols, which play an important role in providing health benefits, particularly as antioxidants. Objective: This study aimed to evaluate the antioxidant activity of avocado leaf kombucha using the Azinobis Ethylbenzothiazoline Sulfonic Acid (ABTS) method. Methods: This research employed an experimental design with quantitative antioxidant activity testing using the ABTS method. The IC₅₀ values were determined through linear regression analysis based on the relationship between sample concentration and percentage inhibition of the ABTS radical. Results: The IC₅₀ value of non-fermented avocado leaf kombucha was 106.40 ppm, which falls within the moderate antioxidant category (IC₅₀: 100–150 ppm). Fermentation for 9 days produced an IC₅₀ of 67.99 ppm (strong), 12 days resulted in 49.91 ppm (very strong), and 14 days resulted in 40.18 ppm (very strong). Vitamin C, used as a positive control, showed an IC₅₀ of 9.160 ppm (very strong). Conclusion: The antioxidant activity of avocado leaf kombucha increased with the duration of fermentation. Non-fermented kombucha exhibited moderate antioxidant activity, while fermentation for 9, 12, and 14 days resulted in strong to very strong antioxidant capacity. Keywords: Kombucha Tea, Avocado Leaves, Antioxidant, ABTS, IC₅₀.